2009
DOI: 10.1021/ic902023u
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Design of Ferromagnetic Molecular Complexes: Magnetostructural Correlations in Ferromagnetic Triply Bridged Dinuclear Cu(II) Compounds Containing Carboxylato and Hydroxo Bridges

Abstract: In the present work we present a comprehensive study of the magneto-structural correlations of a series of ferromagnetic triply heterobridged Cu(II) dinuclear compounds containing [Cu(2)(mu-O(2)CR)(mu-OH)(mu-X)(L)(2)](2+) ions (where X = OH(2), Cl(-), OMe(-) and L = bpy, phen, dpyam) which have the particularity of being all ferromagnetic. The present theoretical study, based on hybrid density functional theory (DFT) calculations, leads to strong conclusions about the role of the pentacoordination geometry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 45 publications
5
55
1
Order By: Relevance
“…However, ferromagnetic interaction was observed in 1 with Cu\O\Cu angle of 146.72°, which may result from the accidental orthogonality of the magnetic orbits. This is not accordance with the reported result that a big bridging angle usually contributes the antiferromagnetic interaction [50]. Since larger dihedral angle between two CuO 2 planes deviated from 180°could lead to weaken antiferromagnetic interactions [1], the dihedral angle of 144.484°in 1 should be an important factor to show ferromagnetic interaction.…”
contrasting
confidence: 68%
“…However, ferromagnetic interaction was observed in 1 with Cu\O\Cu angle of 146.72°, which may result from the accidental orthogonality of the magnetic orbits. This is not accordance with the reported result that a big bridging angle usually contributes the antiferromagnetic interaction [50]. Since larger dihedral angle between two CuO 2 planes deviated from 180°could lead to weaken antiferromagnetic interactions [1], the dihedral angle of 144.484°in 1 should be an important factor to show ferromagnetic interaction.…”
contrasting
confidence: 68%
“…The electron density was described either explicitly considering all electrons or using small core (LANL2) effective core potential (ECP) for the Cu atoms which allows one to take scalar relativistic effects into account. For the all electron calculations we used a rather large standard basis set of Gaussian Type Orbitals (GTO) which is the same as in previous works 11,12 and is defined as follows: 6-3111+G…”
Section: Computational Detailsmentioning
confidence: 99%
“…10 However, to obtain more quantitative relationships it is necessary to go beyond the semiempirical EH method and to make use of more reliable electronic structure methods as demonstrated by recent studies on other triply bridged dinuclear Cu(II) compounds which employed state of art density functional theory (DFT) based methods. 11,12 Six different exchange-correlation functionals have been used in order to fully understand the magnetostructural correlation and also to accurately predict the broad range of magnetic coupling constant (J) values exhibited by class B and class F compounds with ferro-and antiferromagnetic behavior, respectively. The DFT calculations have revealed that, for ferromagnetic class B compounds, the calculated J values almost quantitatively correlate with the sum of Addison's t parameter 13 of each Cu(II) ion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Cu(1)-Cu(1′) distance is 3.3960(3) Å and the Cu(2)-Cu(2′) distance is 3.3365(4) Å, whereas the difference in Cu-O distances at the apical sites is 0.08(1) Å. On the other hand, differences between corresponding bond lengths in the Cu(1) and Cu (2) basal sites are all ≤0.009(2) Å and on average are 0.005(2) Å. Differences within the coordination spheres between corresponding basal bond angles are on average 0.24(7)°and all are ≤0.67(7)°, whereas those involving the apical oxygen atoms are on average 1.99(6)°and range from 0.21(6)°to 3.48(6)°.…”
Section: Resultsmentioning
confidence: 98%
“…[1][2][3][4][5] Although the nuclearity of complexes being reported continues to rise, 6,7 much that is of fundamental significance can be learned from simple systems, 8 the best representatives of which may well be binuclear copper(II) species. For example, the effects of certain specific types of ligands or atoms bridging between pairs of metal atoms are now well understood, but the list of those bridging atoms or ligands is still comparatively small.…”
Section: Introductionmentioning
confidence: 99%